The impact of e-cigarette use in health comumunication on individual perceptions: a psychological analyisis of Islamic education - Nastiti Lutfiah; Qoniah Wijayani (Ikatan Cendikiawan Ilmu Pendidikan Islam (ICIPI), 2024)
The use of e-cigarettes as a topic in health communication creates significant debate and challenges in crafting prevention strategies and public health interventions. E-cigarettes, which are considered a safer alternative to conventional cigarettes, have caused controversy over their health benefits and risks. This article outlines the impact of e-cigarette use in health communication on individual perceptions, focusing on psychological aspects. His research methods can involve a combination of qualitative and quantitative approaches. The results of this study explain that the impact of individual perceptions of e-cigarettes identifies health behaviors that can be positive (avoiding or quitting) or negative (using or increasing consumption). Emphasis on developing communication approaches that consider Islamic values includes steps such as developing health messages that are consistent with Islamic thought, engaging religious leaders, paying attention to cultural context, and crafting messages that can be internalized by Muslim societies. Therefore, this analysis provides valuable insights for health practitioners and educators to design effective and acceptable health communication strategies in Muslim societies.